The dictionary of Bible and Religion (Nashville, Tennessee, 1986)
The book contains more than 880,000 words covering more than 2,800 subjects, names, and places of the Bible and related religious topics. It also describes clearly biblical places, people, and events, leading religious figures, great hymnwriters, missionaries, contemporary religious movements, Jewish beliefs, famous popes, Christian doctrines, religious beliefs throughout history, and major religious groups of the middle East. Complementing the rich book are a host of visual aids and added features, including: 65 color maps of Bible lands, 30 black-and-white line drawings, 28 black-and-white maps, 11 charts and tables, an extensive system of cross-references to articles on related subjects, a "For Further Study" section
Keywords: bible - dictionaries,religions - dictionaries,theology - dictionaries